1994
DOI: 10.1177/0146167294205002
|View full text |Cite
|
Sign up to set email alerts
|

Self and Collective: Cognition and Social Context

Abstract: The relationship between the self and the collective is discussed from the perspective of self-categorization theory. Self-categorization theory makes a basic distinction between personal and social identity as different levels of self-categorization. It shows how the emergent properties of group processes can be explained in terms of a shift in self perception from personal to social identity. It also elucidates how self-categorization varies with the social context. It argues that self-categorizing is inhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,427
0
23

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,787 publications
(1,511 citation statements)
references
References 12 publications
61
1,427
0
23
Order By: Relevance
“…One may question whether the stewardship types presented here are dynamic and context dependent, or transcend specific situations. Social identity theory suggests that individuals have multiple social identities that correspond to widening circles of group membership (Turner et al 1994). The resilience literature also suggests that individuals can adapt their identities to address changes within the socialecological context (Folke et al 2005).…”
Section: Understandings Of Landscape Stewardshipmentioning
confidence: 99%
“…One may question whether the stewardship types presented here are dynamic and context dependent, or transcend specific situations. Social identity theory suggests that individuals have multiple social identities that correspond to widening circles of group membership (Turner et al 1994). The resilience literature also suggests that individuals can adapt their identities to address changes within the socialecological context (Folke et al 2005).…”
Section: Understandings Of Landscape Stewardshipmentioning
confidence: 99%
“…Importantly too, whether she categorizes herself as an individual or as a member of a given group will have important consequences for both her perceptions and her behavior (Turner, Oakes, Haslam & McGarty, 1994).…”
Section: The Social Identity Approach To Creativitymentioning
confidence: 99%
“…We noted above that one of the core predictions of self-categorization theory is that when personal identity is salient, individuals' perceptions will be informed more by their idiosyncratic preferences than when social identity is salient and they are more likely to see the world and act in a manner consistent with group norms (Reicher, 1984;Spears, Lea & Lee, 1990;Wilder & Shapiro, 1984;Turner et al, 1994). When it comes to perceptions of creativity, one implication of this is that when personal identity is salient and a particular group norm is made explicit, people will tend either to ignore the norm or to deviate from it Social identity and creativity 9 as a means of expressing their individuality (Jetten et al, 2002).…”
Section: Social Identity Salience and Group Normsmentioning
confidence: 99%
“…Recent studies have suggested, however, that ethnicity may be a dynamic, fluid part of the social self that varies as a function of the social composition of the settings in which people participate (Turner, Oakes, Haslam, & McGarty, 1994). One aspect of this variability involves ethnic self-awareness, or the extent to which people are consciously aware of their ethnicity at any given moment.…”
mentioning
confidence: 99%